Towards a Greener Future: Using DEMATEL-ANP for Sustainable Indonesian Fiber Cement Board Manufacturing Company - Sri Sulandjari (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2025)
The Indonesian fiber cement board industry faces increasing pressure to enhance sustainability due to growing environmental global concerns and regulatory demands. The companies in this sector must address multiple sustainability criteria such as waste management, resource utilization, and compliance with environmental regulations to remain competitive and sustainable. However, identifying which criteria are the most influential in driving overall sustainability outcomes presents a challenge. Previous studies have often examined these criteria in isolation, without considering their interdependencies. To address this gap, this study integrates the Delphi method with DEMATEL and ANP to analyze and prioritize key sustainability criteria for a fiber cement board company. By developing a comprehensive framework, this research aims to provide actionable insights that will help companies enhance their sustainability performance. In this research, PT. XYZ, a well-known fiber cement board manufacturer in Central Java, Indonesia, was used as a case study. The result shows that the DEMATEL-ANP method reveals that waste management, compliance with environmental regulations, and resource and material management are the most critical criteria, with high prominence and influence scores. These findings suggest that focusing on these critical areas first, followed by processing other criteria accordingly, can significantly enhance the company’s sustainability performance.